STUDI META-ANALISIS: PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Yohannes, - (2021)
This study aims to investigate the effectiveness of implementing the Discovery Learning model on mathematical critical thinking skills of elementary school to high school students comprehensively. The meta-analysis technique was used to analyze the effect size of the primary study. The empirical data of the primary study was obtained through searching the electronic database. The instruments used are coding protocol sheets and coding sheets. Data analysis was carried out with the assistance of the Comprehensive Meta-Analysis (CMA) 3.0 program. The research method used is a systematic review of the results of primary studies in published journal articles. The research sample that met the inclusion criteria was 35 primary studies. Analysis of publication bias and sensitivity showed that all studies included in the analysis were resistant to bias and none of the studies differed significantly from the other studies. The research findings show that overall, the effect of implementing the Discovery Learning model on students' mathematical critical thinking skills is better than the conventional/comparison model, with the level of influence being in the high effect category. Meanwhile, based on the characteristics of the observed study, it was found that there was a significant difference in the influence between groups of the implementation of the Discovery Learning model on mathematical critical thinking skills in terms of education level and research class. On the other hand, there was no difference in the effect between groups when viewed from the characteristics of the year of study, sample size, and duration of treatment. Thus, implementing the Discovery Learning model in mathematics learning is highly recommended because it has a high impact on improving students' critical thinking skills and needs to consider study characteristics such as education level and research class.